2008
DOI: 10.3168/jds.2007-0174
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Treatment of Subclinical Mastitis in Lactating Cows with Penethamate Hydriodide

Abstract: A randomized controlled field trial was performed to evaluate the efficacy of a 3-d treatment regimen with i.m. penethamate hydriodide compared with no treatment in lactating cows with subclinical mastitis. To be included, a cow had to have 2 somatic cell counts (SCC) 300,000 cells/mL at the last 3 monthly controls, 1 or more quarters with SCC >250,000 cells/mL, and the same bacterial species isolated in 2 consecutive samples 2 to 4 d apart. A total of 151 quarters from 92 cows were monitored for 2 mo followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
3
14
1
Order By: Relevance
“…The efficacy of the IM penethamate-based product was 65.8% in our study, which was higher than reported by Salat et al (2008). The earlier study considered subclinical mastitis produced by several mastitis pathogens (S. aureus, CNS S. uberis, non-S. agalactiae streptococci, and Corynebaterium bovis).…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…The efficacy of the IM penethamate-based product was 65.8% in our study, which was higher than reported by Salat et al (2008). The earlier study considered subclinical mastitis produced by several mastitis pathogens (S. aureus, CNS S. uberis, non-S. agalactiae streptococci, and Corynebaterium bovis).…”
Section: Discussioncontrasting
confidence: 77%
“…Other possible predictors of interest not measured in our trial, for example DIM and parity, could affect the cure risks in both treatments. Related to these 2 variables, other authors have reported no influence of the stage of lactation on the cure risk for the penethamate or negative control groups for non-agalactiae streptococci, S. aureus, and CNS (Salat et al, 2008). In contrast, another group of authors reported that for S. aureus treatment, increasing parity was associated with lower cure risk (Barkema et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…administration of penethamate hydriodide for 3 d can be efficacious in the treatment of clinical and subclinical mastitis in lactating cows (Serieys et al 2005;Salat et al 2008). administration of penethamate hydriodide for 3 d can be efficacious in the treatment of clinical and subclinical mastitis in lactating cows (Serieys et al 2005;Salat et al 2008).…”
Section: Discussionmentioning
confidence: 99%